Current Concepts and Controversies in the Management of REM Sleep Behavior Disorder - Matar, E. (Neurotherapeutics, 2021)
Rapid eye movement (REM) sleep behavior disorder (RBD) is characterized by dream enactment and the loss of muscle atonia during REM sleep, known as REM sleep without atonia (RSWA). RBD can result in significant injuries, prompting patients to seek medical attention. However, in others, it may present only as non-violent behaviors noted as an incidental finding during polysomnography (PSG). RBD typically occurs in the context of synuclein-based neurodegenerative disorders but can also be seen accompanying brain lesions and be exacerbated by medications, particularly antidepressants. There is also an increasing appreciation regarding isolated or idiopathic RBD (iRBD). Symptomatic treatment of RBD is a priority to prevent injurious complications, with usual choices being melatonin or clonazepam. The discovery that iRBD represents a prodromal stage of incurable synucleinopathies has galvanized the research community into delineating the pathophysiology of RBD and defining biomarkers of neurodegeneration that will facilitate future disease-modifying trials in iRBD. Despite many advances, there has been no progress in available symptomatic or neuroprotective therapies for RBD, with recent negative trials highlighting several challenges that need to be addressed to prepare for definitive therapeutic trials for patients with this disorder. These challenges relate to i) the diagnostic and screening strategies applied to RBD, ii) the limited evidence base for symptomatic therapies, (iii) the existence of possible subtypes of RBD, (iv) the relevance of triggering medications, (v) the absence of objective markers of severity, (vi) the optimal design of disease-modifying trials, and vii) the implications around disclosing the risk of future neurodegeneration in otherwise healthy individuals. Here, we review the current concepts in the therapeutics of RBD as it relates to the above challenges and identify pertinent research questions to be addressed by future work. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13311-020-00983-7.